Stabilization and Growth in Transition Economies The Early Experience - Fischer, Stanley (International Monetary Fund, 1996)
This paper analyzes the growth and stabilization experience in 26 transition economies in eastern Europe, the former Soviet Union, and Mongolia for the period 1989-1994. Inflation rates have declined significantly in most countries following an inflation stabilization program. Growth resumes after stabilization occurs, typically with a lag of about two years. Reducing inflation thus appears to be a precondition for growth. An econometric analysis of the short-run determinants of inflation and growth illustrates the key roles of fixed exchange rates, improved fiscal balances, and structural reforms in spurring growth and lowering inflation, and confirms that inflation stabilization programs have been beneficial for growth even after controlling for structural reforms